Winter home range sizes of female woodland caribou in the boreal forest of Northwestern Ontario - Romyn, Christina (2019)
Woodland caribou (Rangifer tarandus caribou Gmelin) are listed as “threatened” under the Canadian Species at Risk Act. Fourteen ranges occur within the continuous distribution of caribou in Ontario and have been studied using Global Positioning System (GPS) tracking technology. The Ontario Ministry of Natural Resource and Forestry (OMNRF) employs the use of Argos GPS collars to track caribou movements throughout the province. The purpose of this study was to examine the winter home range sizes of caribou in both a managed and unmanaged forest in northwestern Ontario and to relate winter home range sizes the level of disturbance in the area. Home range sizes were estimated from GPS collaring data using a 95% minimum convex polygon computed using the adehabitatHR package in R statistical programming. Home range sizes were evaluated using simple linear regressions with disturbance as the dependant variable. Home range sizes were most strongly negatively correlated with natural and anthropogenic disturbance in the entire study area (R2 = 0.239). In the unmanaged forest, the level of disturbance was low (20%) home range sizes were large (1580 km2 ± 1374 km2). Conversely, where disturbance was high (42%), especially at the species’ southern range limit, home ranges were low (408 km2 ± 311 km2). In the boreal forest, female caribou may restrict their ranges amid anthropogenic disturbances. Forest harvesting creates small habitat patches that may serve as ecological traps for caribou and increase the risk of predator detection. Therefore, smaller home ranges may serve as an indicator of habitat loss for caribou.